Self-confidence as a Supporting Factor for Public Speaking Skills of Prospective Guidance Teachers - Sari, Azmatul Khairiah; Sari, Rahmahidayati; Nengsi, Ayu Rahma; Wahyuni, Sri Intan (JURNAL PAJAR (Pendidikan dan Pengajaran), 2025)
This research wants to assess self-confidence related to student public speaking skills among BK UNP students, because good public speaking is supported by good self-confidence. The research was carried out using a mixing method using research instruments: questionnaires supported by interviews and observations from 50 students taken at random. The questionnaire has been validated with content validity and empirical validity and produced a validity index of 0.85 and a reliability index of 0.90. This research concludes that BK UNP students have good self-confidence when doing public speaking. From the results of interviews and observations conducted on students, it was found that students should have preparation for appearing in public, both in terms of preparing the material they want to convey and their needs when appearing, overcoming anxiety before appearing, and knowing some common words used by listeners. Due to the limitations of researchers, we only discuss one factor that supports female students' public speaking, namely self-confidence. It is recommended that future researchers conduct research related to public speaking skills in more depth and breadth by looking at other factors that influence public speaking skills and the methods used to improve public speaking skills.